Study of the Implementation of Islamic Leadership (Imamah, Caliph, and Ulil Amri) in Indonesia - Roni Rahmad Hasonangan Ritonga; Zulkarnaen (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to understand and compare the implementation of three main concepts of leadership in Islam Imamah, Khilafah, and Ulil Amri in the socio-political context of democratic and plural Indonesia. Using an explorative-comparative qualitative approach through literature study and critical discourse analysis, this study analyzes classical religious texts, state policy documents, and socio-religious narratives to identify the legitimacy structures, leadership mechanisms, and the relevance of the three concepts to the modern governance system. The findings show that although Imamah and Khilafah have strong theological and historical depths, only the Ulil Amri concept has gained broad legitimacy in Indonesian religious and political discourse. This concept is considered compatible with the principles of constitutional democracy and Islamic ethical values such as amanah, ‘adl, and maslahah. This study formulates a contextual Islamic leadership model that is a synthesis of the three approaches, offering an ethical and functional framework to strengthen governance that is characterful, inclusive, and accountable. These results provide a conceptual contribution to the development of an Islamic leadership paradigm that is relevant to the challenges of the modern nation-state.